SCHEME PLANTING OF SWEET PEPPER IN SUMMER TERM OF CULTIVATION - F. F. Rasulov (Овощи России, 2018)
The sweet pepper varieties ‘Dar Tashkenta’ and ‘Tong’ were included in the State Register of Breeding Achievements in 1980 and 2005 respectively, and recommended for cultivation in the territory of the Republic of Uzbekistan. The planting schemes 70x30 (control), 70x20, 70x40, 70x40/2, 70x50 and 70x50/2 for these varieties were studied. The control variety was ‘Dar Tashkenta’. The feeding area and the number of plants per hectare embodiment was 0.21mІ2 and 47.6 thousand plants; 0.14 mІ2 and 71.4; 0.28 mІ2 and 35.7; 0.28 mІ2 and 71.4; 0.35 and 28.5 mІ2 and 0.35 mІ2 and 57.1 thousand plants. Studies were carried out in summer after harvesting early vegetable crops. During the spring period of the sweet pepper seedlings were planted in the second decade of April, they were planted in the second half of the month of June. It was shown that the planting samples and the density of plant standing had a different effect on the phenological phase of the varieties studied. In the variety of thickened ‘Dar Tashkenta’ (70x20 cm) to rarefied (70x50 cm) planting duration of about a period of from germination to 10% weight of technical maturity of the fruit was increased up to 8-10 days and amounted to 92-99 per day. The ‘Tong’ variety grew for 90-95 days. The phase of 75% of the technical ripeness of fruits in variety ‘Dar Tashkenta’ was for 108-114 days, in Tong for 104-110 days. The planting scheme has an influence on the following measurement parameters: the weight of the roots, the weight of the bush per plant, the number of leaves per plant, the area of the leaf blade, the number of stems of the first and second order, the length and diameter of the fruit, the number of fruits per one fruit set, the mass of fruit and yield. The number of plants from the first planting scheme to the last one was different and ranged from 28.5 to 71.4 thousand per ha. Therefore, the productivity of all varieties is estimated by the number of plants per unit area. Comparing with control (70x30 cm) variant, a low yield was obtained in both varieties with the planting schemes of 70x40 and 70x50 cm, according to the data 20.4 and 18.7 t/ha was in the ‘Tong’ variety 14.2 and 13.6 t/ha. In order to obtain a high yield, the optimal scheme of plant planting was recommended for ‘Dar Tashkenta’ and ‘Tong’: 70x20 and 70x40/2 cm, which corresponds to 71.4 thousand plants per hectare.